1999
DOI: 10.1034/j.1399-0039.1999.540301.x
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s disease, the Silk Road and HLA‐B51: historical and geographical perspectives

Abstract: Behçet's disease (BD), also known as the Silk Road disease, is a blinding inflammatory disorder of young adults found predominantly between the Mediterranean basin and the Orient, and is strongly associated with the major histocompatibility complex (MHC) antigen HLA-B51. In this article we review the history of Behçet's disease since its first description by Hippocrates, the development of the trading routes collectively known as the Silk Road and the effect of population movement on the distribution of HLA-B5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
255
0
13

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(283 citation statements)
references
References 23 publications
6
255
0
13
Order By: Relevance
“…As for the expected weight of evidence, genital ulcerations revealed the greatest value, and skin lesions, PR, ROUs, HLA-B51, ocular lesions, and ileocecal ulcerations in order showed the relatively good performance. However, other features, such as CNS lesions, vascular lesions, peripheral arthritis, and epididymitis, disclosed negligible val- (17). HLA-B51 was separately set as a finding to help for classification or diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…As for the expected weight of evidence, genital ulcerations revealed the greatest value, and skin lesions, PR, ROUs, HLA-B51, ocular lesions, and ileocecal ulcerations in order showed the relatively good performance. However, other features, such as CNS lesions, vascular lesions, peripheral arthritis, and epididymitis, disclosed negligible val- (17). HLA-B51 was separately set as a finding to help for classification or diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…19 Among different genetic markers, the class I HLA-B5 and -B51 gene on chromosome 6p21 is in association with ABD. 20,21 The relative risk of ABD in HLA-B51-positive patients is 13.3 for Turkey, 6.7 for Japan, and 1.3 for the United States of America. 22 HLA-B51 and its suballeles, B5101 and 5121, are important for antigen synthesis of CD8 þ cytotoxic suppressor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a study its prevalence was shown to be as low as 0.4% in Turkey (14). HLA B51, a well-connected allele with BD was also positive in three of our patients and while its prevalence in Turkish BD population is 77%; in healthy Turkish subjects its prevalence was reported to be 26% (15). Thus, as being a rare allele in the Turkish population with a known association with BD, positivity of Cw16 in three patients from the same family was found to be important and it should be investigated further to exclude accidental coincidence.…”
Section: Discussionmentioning
confidence: 99%